The THE EFFECT OF AUTONOMOUS LEARNING BASED ON CHATGPT BASED AUTONOMOUS LEARNING ON IMPROVING STUDENTS' DIVERGENT THINKING - Bima Purba Tangkas; Dian Azizah Sadriansyah Wijaya; Daffa Fakhri Maulana; Sudrajat, Sudrajat (Jurnal Penelitian dan Pendidikan IPS, 2025)
This study is motivated by the importance of developing students' divergent thinking skills in the Society 5.0 era through the use of technology. The purpose of the study was to measure the effect of ChatGPT-based Autonomous Learning on improving students' Divergent Thinking skills. This study applies a quantitative methodology, specifically in a pre-experimental design that uses a measurement pattern before and after treatment on one group of research subjects. The research sample consisted of 32 students of SMP Negeri 8 Yogyakarta who were selected using accidental sampling techniques. The results of the study showed a significant increase in divergent thinking skills, as evidenced by an increase in the average score from 83.906 (pre-test) to 86.625 (post-test) with a significance value of 0.000 (p <0.05). The study concluded that the application of ChatGPT-based autonomous learning is effective in improving students' divergent thinking skills, but it needs to be balanced with supervision and understanding of academic ethics to minimize the negative impacts of technology use.